The influence of project leaders’ behavioral competencies on the performance of Six Sigma projects - Marzagão, Daniela Santana Lambert; Carvalho, Marly Monteiro de (Review of Business Management, 2016)
Purpose – This article aims to characterize behavioral competencies of Six Sigma Project Leaders, as well as relate those competencies with projects performance. Design/methodology/approach – It is a survey-based research. This study analyzes 225 Six Sigma Projects in Brazil, Chile and Colombia, led by 191 Project Leaders. Findings – The projects were classified accordingly with their performance and project leaders had their behavioral characteristics mapped. Based on independence statistical testing, it was identified that project success depends on both competencies of the project leader, innovation and direction. Originality/value – The article shows the relationship between behavioral competencies and project performance. In addition, the article maps behavioral competencies in six sigma projects.